Students' Mathematical Numeracy Ability in Grade IV in terms of Learning Interest on Squared Numbers - Erdi Guna Utama; Nurhaliza Nurhaliza; Slamat Fitriyadi; Usina Robert Moseki (International Journal of Multi Discipline Science, 2023)
This study aims to (1) describe students' mathematical numeracy ability; (2) describe the level of students' numeracy ability in terms of learning interest and (3) describe the factors that influence students' mathematical numeracy ability. This research method was qualitative descriptive research. The research subjects were 45 grade IV students at SD Negeri 84 Singkawang. Data collection techniques in this study were based on questionnaires, measurements and interviews. The data analysis technique used Miles and Huberman Model, namely data reduction, data presentation, and drawing conclusions. The results showed that (1) students' mathematical numeracy ability in solving problems on flat material had an average of 39.58 which was in the medium category, (2) students' mathematical numeracy ability in terms of learning interest had an average of 67.75 which was in the high category (a) students' mathematical numeracy ability in terms of high interest in learning were able to carry out all indicators very well and had an average of 38.64; (b) students' mathematical numeracy ability in terms of medium interest in learning was able to carry out all indicators well and had an average of 39; and (c) students' mathematical numeracy ability in terms of low interest in learning; students were able to solve problems well and had an average of 44.33, (3) Students’ mathematical numerical ability influenced by internal factors, namely, the ability to remember, study habits, and interest in learning, while for external factors, namely family, community, and friends environments.